A review of recent research on the antimicrobial activities of thiosemicarbazone-based compounds - Gürsel Korkmaz (Journal of New Results in Science)
Thiosemicarbazones can be synthesized by condensation of thiosemicarbazides with ketones or aldehydes and play a role as precursors in the synthesis of many compounds such as thiazoles. They can exhibit many biological activities such as anti-inflammatory, antitumor, and antimicrobial properties. The discovery of antibiotics was an important milestone in the treatment of bacterial infections. However, antimicrobial resistance developed by microorganisms has created the need to discover new antimicrobial agents. Thiosemicarbazones and thiosemicarbazone-based compounds show significant antimicrobial potential. This review investigates the antimicrobial activity results of 244 Thiosemicarbazones and Thiosemicarbazone-based compounds over the last five years. We summarized some articles on thiosemicarbazones and their hybrids showing only antibacterial and antifungal activity in Web of Science (WOS) between 2019 and 2024.